Pengaruh Manajemen Keuangan Terhadap Efektivitas dan Efisiensi Lembaga PAUD - Rahman, Lutfi Kausar; Suhendar, Asep Dadan; Fauzia, Annisa Eka (POLITEKNIK LP3I, 2024)
Most PAUD Institutions are still obstacles in managing their finances, especially for small-scale institutions. The importance of financial management is applied well to be able to allow PAUD institutions to allocate each resource its resources effectively and efficiently. So the purpose of this study was to investigate and analyze the influence of financial management on the effectiveness and efficiency of the PAUD Agency, especially in Nurun Nisa TK. The method used is qualitative, because researchers do not use questionnaires in performing their research, and by using a comparaive research approach, namely understanding the cause-effect relationship between financial management, effectiveness, and efficiency. Data collection techniques were carried out through interviews, direct observation and analyzed financial statements on Nisa's Nurun Nisa. The results showed that there was a positive relationship between financial management practices and good level of effectiveness and PAUD agency efficiency in Nurun Nisa TK. There has been an increase in each July-December 2022 and January-June 2023, with the percentage of effectiveness ratios from 88.41% to 91.55%, revenue efficiency from 66.1% to 58.99%, and operational efficiency of 82.11% to 77.01%. So the existence of good level of effectiveness and efficiency in Nurun Nisa TK provides concrete evidence that the optimal implementation of financial management can directly contribute to increased effectiveness of education quality and resource use efficiency.